Effectiveness and safety of Shugan Jianpi (SGJP) formula in the treatment of nonalcoholic steatohepatitis (NASH): A protocol for systematic review and meta-analysis of randomized controlled trials. Issue 51 (23rd December 2021) - Chen, Mingtai; Gu, Yanghui; Huang, Furong; Zhong, Guofu; Men, Ling; Liu, Qiang; Luan, Jienan; Tong, Guangdong
Abstract: Background: It is known that nonalcoholic steatohepatitis (NASH) has been more and more popular in clinical practice. Apart from lifestyle modification, pharmacological therapy treating NASH has still been limited and insufficient. A growing number of studies demonstrated that Shugan Jianpi (SGJP) formula, as a kind of Chinese herbal medicine prescription, could improve blood lipid indexes, liver function, and other clinical measures in NASH patients. Nevertheless, there still has been a lack of study to systematically assess the efficacy and safety of SGJP formula treating NASH. Therefore, it is necessary to conduct this systematic review and meta-analysis. Methods: A systematic literature search for articles up to December 2021 will be performed in following electronic databases: MEDLINE, Embase, the Cochrane Library, China National Knowledge Infrastructure, Chinese Scientific Journals Database Database, Chinese Biomedical Database, Chinese Biomedical Literature Service System, and Wanfang Database. Inclusion criteria are randomized controlled trials of SGJP formula applied on NASH patients. The primary outcome measures will be liver function, blood lipid indexes, ultrasound, or radiological imaging examination. The safety outcome measures will be adverse events and kidney function. RevMan 5.3 software will be used for data synthesis, sensitivity analysis, subgroup analysis, and risk of bias assessment. A funnel plot will be developed to evaluate reporting bias. Stata 12.0 will be used for meta-regression and Egger tests. We will use the Grading of Recommendations Assessment, Development and Evaluation system to assess the quality of evidence. Discussion: This study will provide a high-quality synthesis of the efficacy and safety of SGJP for NASH patients. Ethics and dissemination: This systematic review does not require ethics approval and will be submitted to a peer-reviewed journal. Trial registration number: PROSPERO CRD42021259097.